Study of Phenomenology in Female Football Fans, Persib Bandung Club - Windi Fitriyani; Oky Oxcygentri; Nurkinan Nurkinan (CHANNEL: Jurnal Komunikasi, 2021)
Speaking of football, many are involved in it including football supporters. Supporters are the people who provide support in a football match. Today, the stadium is dominated not only by men, but many of the women. This relates to the motives of female fans of Persib Bandung football club. This research aims to find out the experiences, motives and meanings of women fans of Persib Bandung football club. The method used in this study is a qualitative method with a phenomenological approach. Based on the results of the research that has been done, it can be concluded that the motives of women fans of Persib Bandung football club have two categories namely motive cause (because motive) consisting of: Geographical Location Motive and Popularity Level Motif. While the motive of hope (in order to motive) or the motive of the destination, namely: Motif Support Directly In the Stadium, Entertainment Motif and Motif Got A Partner.